2004
DOI: 10.1246/cl.2004.728
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dimerization, Alkoxylation, and Sulfidation of Olefins Catalyzed by RuCl3·nH2O

Abstract: Novel ruthenium-catalyzed reactions that employ ruthenium trichloride n-hydrate (RuCl3·nH2O) were investigated and dimerization, alkoxylation and sulfidation of olefins were noted. Adducts of Markovnikov type and anti-Markovnikov type were obtained in a stereospecific manner and in good yield, depending on the type of olefins used as the starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In the presence of 1 mol % of carbene A and 1 mol % of benzoic acid as cocatalyst, benzoin (8), the Michael addition product of benzoin to DMAA (9), and the lactone (10) were formed. 12 The molecular structure of the Michael product 9 was unambiguously proven by X-ray crystallography ( Figure 1).…”
Section: The Reaction Of Dmaa With Benzaldehyde Catalyzed By Nhc Amentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of 1 mol % of carbene A and 1 mol % of benzoic acid as cocatalyst, benzoin (8), the Michael addition product of benzoin to DMAA (9), and the lactone (10) were formed. 12 The molecular structure of the Michael product 9 was unambiguously proven by X-ray crystallography ( Figure 1).…”
Section: The Reaction Of Dmaa With Benzaldehyde Catalyzed By Nhc Amentioning
confidence: 99%
“…Sakakibara et al reported the Ru catalyzed dimerization of DMAA, along with the formation of a small amount of a non-characterized trimer. 9 In recent years, our group has studied intermediates of the NHC-catalyzed Umpolung of aldehydes. 10 Herein we report the tail-to-tail oligomerization of DMAA, the NHC-catalyzed cross coupling of DMAA with MMA, and the attempted Stetter reaction of benzaldehyde with DMAA.…”
mentioning
confidence: 99%
“…To the best of our knowledge, 1,1‐diarylethenes 8 (Scheme ) usually give indan products similar to 5 through cyclodimerization in the presence of Lewis acids, such as EtAlCl 2 ,9a RuCl 3 ⋅ n H 2 O,9b InBr 3 ,9c and BiCl 3 ,9d or aminium hexachloroantimonates 10. There is one example of aminium salt promoted heterodimerization of 1,1‐diphenylethene 8 a (Ar=Ph) with vinylferrocene, which occurs in 62 % yield, along with a 10 % yield of the head‐to‐tail dimer of vinylferrocene 10d.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction proceeds with Markovnikov selectivity in both C−C bond forming steps. Several Lewis acids, including FeCl 3 , AlCl 3 , BiCl 3 , and RuCl 3 , and also Brønsted acids have been reported to catalyze this reaction . Unsaturated dimers are important chain‐transfer reagents in the production of polymers .…”
Section: Introductionmentioning
confidence: 99%